DIVERSIFIED GROWTH STRATEGIES AND DETERMINATION OF OPTIMAL BOUNDS OF LARGE INDUSTRIAL BUSINESS GROUPS - N. V. Linder (Стратегические решения и риск-менеджмент, 2014)
Methodical approaches to process of formation of strategy of diversified growth of the large industrial enterprise are considered diversification strategy from positions of ensuring steady competitive advantages of industrial business groups. Diversified growth is inseparably linked with determination of the optimum size of the company which is defined by criterion of specialization within all integrated system. Examples of the main directions of diversified growth of the Russian industrial companies are given.